Foundation Flex for Designers - Goralski, Greg; Leon, Lordalex (Apress : Imprint: Apress, 2008)
All Flex applications look the same-a blue-gray background and silver-skinned components-right? That doesn't have to be the case, though. This book shows you how to ensure that your Flex 2 and 3 projects stand out from the crowd and provide your users with an application that is both visually stunning and beautifully functional. Flex Builder, coupled with the Adobe Creative Suite (CS3), is a powerful combination, providing all the tools you need to create compelling, vibrant interfaces. This book guides you through creating applications with Flex Builder, designing layouts in Fireworks, creating custom skins for your components in Photoshop and Illustrator, and using CSS to enhance the appearance of your rich Internet applications (RIAs). You'll learn how to efficiently use and style states, enabling you to switch between "pages", thus adding real depth to your applications. You'll also learn how to build web forms that are intuitive to use, helping your users provide the information you're after. Your Flex applications no longer have to be contained within a web browser window-Adobe Integrated Runtime (AIR) enables the creation of desktop applications. This book explores giving an AIR application a truly custom shape and style, leaving the rectangular form that defines most applications far, far behind. Flex isn't just for programmers; it's time for designers to take back RIAs and show what that "R" really stands for. The Internet is not just about collecting data-it's about visual communication and giving people a rich user experience, and that's what designers do best.